Design and Application of Rapid Dewatering for Tailings Containing Sodium Silicate: Laboratory and Industrial Test Results. (28th February 2020) - Sun, Guoquan; Zhou, Keping; Kang, Qian; Wang, Daolin; Xiao, Chongchun
Abstract : Focusing on the tailings containing high sodium silicate (water glass), this study conducted laboratory experiments and semi-industrial tests of flocculation and sedimentation for rapid tailings dewatering. Various reagent combinations, lime and anionic flocculant (APAM) (L&A), sulfuric acid and APAM (S&A), and calcium chloride and APAM (C&A), were tested. The results show that (i) all the three combinations presented a good effect in the laboratory experiments, and the relatively optimum dosages were L&A of 2 kg/t & 30 g/t, S&A of 2.6 kg/t & 20 g/t, and C&A of 3 kg/t & 30 g/t. (ii) The overflow water of the L&A group became turbid after 10 hours, and the pH increased to 14. While, for the S&A and C&A groups, the solid content in overflow wastewater (SCOW) fluctuated over time but could be mostly controlled in 300 ppm. The pH declined from 7 to 4 with time in the S&A group, and it was 7-8 in the C&A group. (iv) Thus, a backfill system with dewatering technology based on the C&A combination was designed. In the field application, the overflow water was recycled with the SCOW of less than 250 ppm and the pH of 7.5, while the underflow concentration was greater than 70 wt.%. The achievement provides a way to utilize the tailings containing sodium silicate effectively and environmentally, which will reduce the tailings dam on the Earth.